Outer-membrane permeabilization, LPS transport inhibition: activity, interactions, and structures of thanatin derived antimicrobial peptides - Swaleeha Jaan Abdullah (2024)
Currently, viable antibiotics available to mitigate infections caused by drug-resistant Gram-negative bacteria are highly limited. Thanatin, a 21-residue-long insect-derived antimicrobial peptide (AMP), is a promising lead molecule for the potential development of novel antibiotics. Thanatin is extremely potent, particularly against the Enterobacter group of Gram-negative pathogens, e.g., E. coli and K. pneumoniae. As a mode of action, cationic thanatin efficiently permeabilizes the LPS-outer membrane and binds to the periplasmic protein LptAm to inhibit outer membrane biogenesis. Here, we have utilized N-terminal truncated 16- and 14-residue peptide fragments of thanatin and investigated structure, activity, and selectivity with correlating modes of action. A designed 16-residue peptide containing D-Lys (dk) named VF16 (V1PIIYCNRRT-dk-KCQRF16) demonstrated killing activity in Gram-negative bacteria. The VF16 peptide did not show any detectable toxicity to the HEK 293T cell line and kidney cell line Hep G2. As a mode of action, VF16 interacted with LPS, permeabilizing the outer membrane and binding to LptAm with high affinity. Atomic-resolution structures of VF16 in complex with LPS revealed cationic and aromatic surfaces involved in outer membrane interactions and permeabilization. Further, analyses of an inactive 14-residue native thanatin peptide (IM14: IIYCNRRTGKCQRM) delineated the requirement of the β-sheet structure in activity and target interactions. Taken together, this work would pave the way for the designing of short analogs of thanatin-based antimicrobials.